Response strategies to acute and chronic environmental stress in the arctic breeding Lapland longspur (Calcarius lapponicus) - Zhou Wu; Matthew M. Hindle; Valerie R. Bishop; Angus M. A. Reid; Katarzyna Miedzinska; Jonathan H. Pérez; Jesse S. Krause; John C. Wingfield; Simone L. Meddle; Jacqueline Smith (Communications Biology)
Abstract The potentially devastating effects of climate change have raised awareness of the need to understand how the biology of wild animals is influenced by extreme-weather events. We investigate how a wild arctic-breeding bird, the Lapland longspur (Calcarius lapponicus), responds to different environmental perturbations and its coping strategies. We explore the transcriptomic response to environmental adversity during the transition from arrival at the breeding grounds to incubation on the Arctic tundra. The effects of an extremely cold spring on arrival and a severe storm during incubation are examined through RNA-seq analysis of pertinent tissues sampled across the breeding cycle. The stress response, circadian rhythms, reproduction, and metabolism are all affected. A key gene of the Hypothalamic-Pituitary-Adrenal axis, FKBP5, was significantly up-regulated in hypothalamus. The genome assembly and gene expression profiles provide comprehensive resources for future studies. Our findings on different coping strategies to chronic and acute stressors will contribute to understanding the interplay between changing environments and genomic regulation.